Origins of the Greek verb - Willi, Andreas 1972- (Cambridge University Press, 2018)
Situated at the crossroads of comparative philology, classics and general historical linguistics, this study is the first ever attempt to outline in full the developments which led from the remotest recoverable stages of the Indo-European proto-language to the complex verbal system encountered in Homer and other early Greek texts. By combining the methods of comparative and internal reconstruction with a careful examination of large collections of primary data and insights gained from the study of language change and linguistic typology, Andreas Willi uncovers the deeper reasons behind many surface irregularities and offers a new understanding of how categories such as aspect, tense and voice interact. Drawing upon evidence from all major branches of Indo-European, and providing exhaustive critical coverage of scholarly debate on the most controversial issues, this book will be an essential reference tool for anyone seeking orientation in this burgeoning but increasingly fragmented area of linguistic research